Digital Learning Media in Interactive Multimedia Based on Inquiry Approach for Sociology Learning in High Schools - Pinilih, Yogi; Rejekiningsih, Triana; Musadad, Akhmad Arif (JTP - Jurnal Teknologi Pendidikan, 2024)
The rapid evolution of technology presents significant challenges in its integration into educational environments. Despite these challenges, interactive multimedia digital learning materials stand out as an effective means to meet educational objectives in high schools. By combining these materials with methodologies like inquiry-based learning, educators can offer a richer and more dynamic learning experience. Therefore, the objective of this research is to develop interactive multimedia with an inquiry-based approach that is suitable for use in education. The research method used in this study is research and development, adopting the Alessi & Trollip model. The research sample consist of 7 people which was media experts, subject matter experts, practitioners (subject teachers), and 42 students. Data collection is conducted through non-test methods such as observation and questionnaires. The research data is then analyzed qualitatively and quantitatively. The research results show that in the alpha testing phase, the developed interactive multimedia received a "Very Good" qualification from the experts and practitioners who acted as validators, with an overall average score of 87%. Meanwhile, the beta testing results with the research subjects, the students, gave a rating of 87% which falls under the "Very Good" qualification. Thus, interactive multimedia with an inquiry-based approach is deemed suitable for use as a learning medium in sociology subjects. This research showed that the inquiry-based multimedia for sociology could be a tool to facilitate learning activities in high schools.